2022
DOI: 10.3390/min12070813
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Small-Scale Heterogeneity at the Core–Mantle Boundary Using Sample Entropy of SKS and SPdKS Synthetic Waveforms

Abstract: Qualitative and quantitative analysis of seismic waveforms sensitive to the core–mantle boundary (CMB) region reveal the presence of ultralow-velocity zones (ULVZs) that have a strong decrease in compressional (P) and shear (S) wave velocity, and an increase in density within thin structures. However, understanding their physical origin and relation to the other large-scale structures in the lowermost mantle are limited due to an incomplete mapping of ULVZs at the CMB. The SKS and SPdKS seismic waveforms is ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…This is similar to the ULVZ strength parameter defined in Pachhai, Thorne, et al. (2022) and Rondenay et al. (2010) and provides another way of assessing whether or not a ULVZ is required to fit these data.…”
Section: Results For Observed Datamentioning
confidence: 58%
See 1 more Smart Citation
“…This is similar to the ULVZ strength parameter defined in Pachhai, Thorne, et al. (2022) and Rondenay et al. (2010) and provides another way of assessing whether or not a ULVZ is required to fit these data.…”
Section: Results For Observed Datamentioning
confidence: 58%
“…We generated random noise by convolving a Gaussian auto‐correlation function (ACF) with a series of random numbers similar to that in Pachhai, Thorne, et al. (2022). Here we define the Gaussian ACF as: normalAnormalCnormalF(t)=σet2/Tnormalcnormalonormalrnormalnnormalenormalr2, $\mathrm{A}\mathrm{C}\mathrm{F}(t)=\sigma {e}^{-{t}^{2}/{T}_{\mathrm{c}\mathrm{o}\mathrm{r}\mathrm{n}\mathrm{e}\mathrm{r}}^{2}},$ where T corner is the corner period, and σ is the root‐mean‐square (RMS) of the noise.…”
Section: Synthetic Experimentsmentioning
confidence: 99%
“…It has also been suggested that ultra‐high velocity zones (UHVZs) may exist along the CMB as well (e.g., Yu et al., 2018; Garnero et al., 2020; Pachhai et al., 2022b). The PdP reflection from this type of structure could potentially look similar to the ULVZ DAS results since the difference in polarity is removed when the PcP waveforms are enveloped (Section 2.5).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike ULVZs, the seismic characteristics of UHVZs have not been extensively investigated. Studies that have examined UHVZs have used S‐wave phases (e.g., Yu et al., 2018; Garnero et al., 2020; Pachhai et al., 2022b) and have estimated that the corresponding V S is ∼10% higher than PREM. That said, these investigations provide no constraints on the potential V P increase within UHVZs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation